A Survey on Crop Yield Prediction using Machine Learning - et. al., Vishal Nathgosavi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In a country within the economy of the state, the agricultural sector plays a vital role. several advances within the field of agriculture have conjointly been enforced in recent years. Serious analysis is happening everywhere the planet with the event of IoT, massive knowledge technology and machine learnings regarding however farmers and even the govt. square measure learning a way to do this. whereas the fortification of agriculture may be classified and analyzed in several areas, like crop management, ground management, weed identification, water management, yield management, eutherian management, we'll think about crop yield management as a result of we have a tendency to believe it to be the surroundings within which an excellent deal of technical progress goes to permit the farmer to urge his crop to his right level. during this article, we'll study specially machine learning and profound learning ways of varied researchers likewise as their impact within the agriculture business on crop yield management.